CLINICAL EFFECTIVENESS OF INSULIN GLARGINE & ASPART VERSUS NPH & REGULAR INSULIN RÉGIME IN TYPE 1 DIABETIC PATIENTS OF PAKISTAN - Dr. Zahid Shehzad Siddiqui; Saba Majeed; Shagufta Sikander; Tauseef Ahmed; Sadia Kashif; Aisha Aziz; Syed Ali Jasim Rizvi; Hiba Kanwal Majeed (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
The present comparative analysis to evaluates the clinical safety and efficacy of insulin glargine & ASPART versus NPH & regular insulin régime in type 1 diabetic patients of Pakistan. The present comparative study conducted at across multiple tertiary care hospitals in different regions of Pakistan. This study was employing a multicenter, prospective, randomized, open-label, parallel-group design to ensure a robust and comprehensive evaluation of the clinical safety and efficacy. A six-month study period was allowed for sufficient follow-up time. The study was employing a non-probability consecutive sampling technique for participant recruiting two groups, Group A (n=100) Insulin Glargine/Aspart Regimen and Group B: (n=100) NPH/Regular Insulin Regimen. Continuous variables, such as HbA1c levels, fasting blood glucose, lipid profiles, and weight measurements, was be summarized using descriptive statistics, including means and standard deviations. There is no significant difference regarding glycemic control and lipid profile between two groups Insulin Glargine/Aspart and NPH/Regular Insulin. Baseline characteristics were similar across both groups, ensuring comparability. Significant improvements in glycemic control were observed in the Insulin Glargine/Aspart group, with HbA1c levels at 7.5 ± 1.1% compared to 8.2 ± 1.4% in the NPH/Regular Insulin group (p>0.05). FBS and PBS levels were also lower in the Insulin Glargine/Aspart group (p>0.05 and P p>0.05, respectively). There was no significant difference in daily insulin dosage (p0.05) and hypoglycemic episodes. The Insulin Glargine/Aspart regimen demonstrates superior clinical efficacy and a better safety profile compared to the NPH/Regular Insulin regimen in Type 1 diabetic patients in Pakistan. These findings support the preferential use of Insulin Glargine/Aspart for enhanced glycemic control and reduced adverse effects. The comparative analysis of Insulin Glargine/Aspart versus NPH/Regular Insulin regimens reveals that Insulin Glargine/Aspart provides significantly better glycemic control and fewer adverse effects in Type 1 diabetic patients in Pakistan. These results advocate for the adoption of Insulin Glargine/Aspart to improve treatment outcomes and patient safety in this population.